Investigating the Role of Perceived Brand Quality and Normative Influence on Prestige Branded Apparel Purchase Intention of Youths in Malaysia - Jeannot Abdul Karim; Lew Sue Ling; Sofiah Abd. Rahman; Shishi Kumar Piaralal, (Open University Malaysia (OUM), 2015)
Luxury or prestige brands have been bought by consumers for various reasons such as to project status or to project an identity. The aim of this study is to investigate the relationship between perceived quality of prestige brands and apparel purchase intention. Additionally, the relationship between normative influence and apparel purchase intention is also investigated. The focus of the study is on the effects of the constructs stated on purchase intention among youths in Malaysia. The study specifically focuses on youths in Malaysia due to the fact that Malaysia is considered a demographically young nation with 60 percent of the population under the age of 30 and having a population where the median age is 28. Questionnaires were distributed using a convenient sampling method to students from a local university. Descriptive analysis was done on the data collected and the stated constructs were tested on reliability and validity. The relationship between the constructs was then tested using structural equation modeling. Findings of the study indicated that the perceived quality of prestige brands and normative influence have a positive relationship with apparel purchase intention behavior among youths in Malaysia. The study provides insights to apparel retailers on the role of perceived quality of prestige brands and normative roles towards apparel purchase intention. [abstract by authors]